Growth Inhibition Kinetics of a Pseudomonas Diesel-degrading Strain from Antarctica (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2019)
Antarctica is one of the largest southernmost continent and most pristine wilderness areas left on earth. Over decades, human activities in this area have resulted in the accumulated pollution of hydrocarbon in the Antarctica mainly due to transportation and logistics activities. The sinking of the supply ships Nella Dan and Bahia Paraiso have resulted in diesel spillage that warrant the utilization and research on diesel-degrading microorganisms in the form of bioremediation to prepare for future disasters. A previously isolated diesel-degrading Pseudomonas sp. strain DRYJ3 has shown effectiveness as a bioremediation tool. Its growth is however strongly inhibited as the diesel concentrations was increased. In this study the inhibitory effect of diesel on the growth rate of this bacterium is modelled according to the Luong, Aiba, Haldane, Hans-Levenspiel, Yano, Teissier and Monod models. Statistical evaluations indicated that the most suitable kinetic model to fit the growth rate on diesel was Luongâ€™s model. The Luongâ€™s constants; maximal growth rate, half saturation constant for maximal growth, maximum substrate concentration that growth ceases, and curve parameter that defines the steepness of the growth rate decline from the maximum rate symbolized by ïmax, Ks, Sm, and n were 0.406 hr-1 (95% CI, 0.269 to 0.881), 0.194 (%v/v) (95% CI, 0.2877 to 0.390), 4.025 (%v/v) (95% CI, 3.820 to 4.229) and 0.378 (95% CI, 0.122 to 0.877) 0.099, respectively. The Luong model predicted Sm value was close to the value of which no growth was observed experimentally suggesting the appropriateness of the model in adhering to observed values.
Keywords: Pseudomonas sp.; Antarctica; diesel-degrading; growth kinetics; Luong